Competencies of English for Academic Purposes Educators at Engineering Universities: A Conceptual Framework - Nor Yazi, Khamis; Supyan, Hussin; Nor Fariza, Mohd Nor (IDOSI Publication, 2014)
This study proposes a conceptual framework in identifying specific competencies for English for Specific Academic Purposes (ESAP) ESL educators teaching at engineering universities. The increasing demand for effective language and communication skills in engineering fields has prompted the need for quality ESAP educators. However, few studies specify on finding the required competencies for the educators. Hence, this paper aims to conceptualise a framework of competencies for Malaysian ESL EAP educators’ teaching at engineering universities. Structured by three elements from the Malaysian Teacher Education [1] i.e. Values, Knowledge and Skills to define the competencies, the framework is supported by the ESP Learning Centred Approach by Hutchinson and Waters [2] and Critical EAP Theory by Benesch [3]. Three international frameworks, the Professional Service Standards for ELT [4], the Competencies for Teachers of English in Engineering Colleges [5]and BALEAP TEAP Competency Framework [6] were adapted in identifying the competency items for the educators. The study proposes mixed methods of Delphi and survey techniques. The proposal aimstoelevate the educators’ quality teaching and professional standards.